2022
DOI: 10.1093/cei/uxac086
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maternal anti-alpha-enolase antibody expression on the brain development in offspring

Abstract: Anti-alpha-enolase autoantibodies have not only been found to play an important role in autoimmune diseases, but also cause neurological damage in adults. In this study, a pregnant mouse model with high serum alpha-enolase (ENO1)-specific antibody (ENO1Ab) was established by immunization with ENO1 protein to explore the effects of maternal circulatory ENO1Ab on the brain development in offspring. The pups showed impaired learning and memory abilities with obviously thinner tight junctions in the brain tissue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Circulating ENO1Ab has been proposed to act as a potential biomarker for that disease [ 19 ]. It has been reported that ENO1Ab not only caused tissue cell injury through mediating antibody-dependent cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC), but also directly recognized the membrane-bound ENO1 protein and interfered with its functions [ 18 , 19 , 35 , 36 ]. All these findings indicate that ENO1Ab may play an important role in the pathogenesis of spontaneous abortion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating ENO1Ab has been proposed to act as a potential biomarker for that disease [ 19 ]. It has been reported that ENO1Ab not only caused tissue cell injury through mediating antibody-dependent cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC), but also directly recognized the membrane-bound ENO1 protein and interfered with its functions [ 18 , 19 , 35 , 36 ]. All these findings indicate that ENO1Ab may play an important role in the pathogenesis of spontaneous abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent in vitro study has shown that ENO1-specific IgG could directly reduce β-hCG and progesterone production of cultured trophoblast cells, indicating a potential mechanism of causing miscarriage [ 19 ]. In addition, in vivo studies have found that ENO1Ab could damage cells through ADCC and CDC [ 18 , 35 ]. The constructive expression of ENO1 in the placenta [ 16 ] and increased production of P6Abs in AIT women suffering from miscarriage suggest that ENO1-P6Ab might injure the placenta and embryo through ADCC and/or CDC.…”
Section: Discussionmentioning
confidence: 99%